Sex-dependent host-microbiome dynamics in zebrafish: Implications for toxicology and gastrointestinal physiology - Martyniuk, Christopher J; Buerger, Amanda N; Vespalcova, Hana; Rudzanova, Barbora; Sohag, Shahadur R; Hanlon, Amy T; Ginn, Pamela E; Craft, Serena L; Smetanova, Sona; Budinska, Eva; Bisesi, Joseph H; Adamovsky, Ondrej (Comparative biochemistry and physiology. Part D, Genomics & proteomics, 2022)
The physiology of males and females can be vastly different, complicating interpretation of toxicological and physiological data. The objectives of this study were to elucidate the sex differences in the microbiome-gastrointestinal (GI) transcriptome of adult zebrafish. We compared microbial composition and diversity in both males and females fed the same diet and housed in the same environment. There were no sex-specific differences in weight gain nor gastrointestinal morphology based on histopathology. There was no difference in gut microbial diversity, richness (Shannon and Chao1 index) nor predicted functional composition of the microbiome between males and females. Prior to post-hoc correction, male zebrafish showed higher abundance for the bacterial families Erythrobacteraceae and Lamiaceae, both belonging to the phyla Actinobacteria and Proteobacteria. At the genus level, Lamia and Altererythrobacter were more dominant in males and an unidentified genus in Bacteroidetes was more abundant in females. There were 16 unique differentially expressed transcripts in the gastrointestinal tissue between male and female zebrafish (FDR corrected, p < 0.05). Relative to males, the mRNA expression for trim35-9, slc25a48, chchd3b, csad, and hsd17b3 were lower in female GI while cyp2k6, adra2c, and bckdk were higher in the female GI. Immune and lipid-related gene network expression differed between the sexes (i.e., cholesterol export and metabolism) as well as networks related to gastric motility, gastrointestinal system absorption and digestion. Such data provide clues as to putative differences in gastrointestinal physiology between male and female zebrafish. This study identifies host-transcriptome differences that can be considered when interpreting the microgenderome of zebrafish in studies investigating GI physiology and toxicology of fishes.
Keywords: Gastrointestinal Microbiome; mikrobiota; Female; dánio pruhované; Sex differences; Microbiota; zvířata; Microgenderome; Apoptosis Regulatory Proteins; Zebrafish; ženské pohlaví; Male; Gene networks; Experimental design; proteiny regulující apoptózu; střevní mikroflóra; Bacteria; Animals; mužské pohlaví; Gastrointestinal Tract; gastrointestinální trakt; Gastrointestinal system